The shield and the sabre the Desert Rats in the Gulf, 1990-91 - Pearce, Nigel (HMSO, 1992)
"In between October 1990 and February 1991, the British Army transported 35,000 troops and their equipment from Europe to Saudi Arabia in its largest logistic operation since the Second World War ... This book is effectively the British Army's account of its role in containing further Iraqi aggression after the unprovoked invasion of Kuwait, and liberating the sheikhdom from Saddam Hussein's occupying forces ... [This account is] illustrated with 200 photographs, maps, and technical drawings"